Combination Approaches to Target PD-1 Signaling in Cancer - Moore, Emily K.; Strazza, Marianne; Mor, Adam (Frontiers in Immunology, 2022)
Abstract Cancer remains the second leading cause of death in the US, accounting for 25% of all deaths nationwide. Immunotherapy techniques bolster the immune cells’ ability to target malignant cancer cells and have brought immense improvements in the field of cancer treatments. One important inhibitory protein in T cells, programmed cell death protein 1 (PD-1), has become an invaluable target for cancer immunotherapy. While anti-PD-1 antibody therapy is extremely successful in some patients, in others it fails or even causes further complications, including cancer hyper-progression and immune-related adverse events. Along with countless translational studies of the PD-1 signaling pathway, there are currently close to 5,000 clinical trials for antibodies against PD-1 and its ligand, PD-L1, around 80% of which investigate combinations with other therapies. Nevertheless, more work is needed to better understand the PD-1 signaling pathway and to facilitate new and improved evidence-based combination strategies. In this work, we consolidate recent discoveries of PD-1 signaling mediators and their therapeutic potential in combination with anti-PD-1/PD-L1 agents. We focus on the phosphatases SHP2 and PTPN2; the kinases ITK, VRK2, GSK-3, and CDK4/6; and the signaling adaptor protein PAG. We discuss their biology both in cancer cells and T cells, with a focus on their role in relation to PD-1 to determine their potential in therapeutic combinations. The literature discussed here was obtained from a search of the published literature and ClinicalTrials.gov with the following key terms: checkpoint inhibition, cancer immunotherapy, PD-1, PD-L1, SHP2, PTPN2, ITK, VRK2, CDK4/6, GSK-3, and PAG. Together, we find that all of these proteins are logical and promising targets for combination therapy, and that with a deeper mechanistic understanding they have potential to improve the response rate and decrease adverse events when thoughtfully used in combination with checkpoint inhibitors.